Smart Irrigation System Techniques using Artificial Intelligence and IoT - Dharashive, Prashant; Sawale, Manish (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Combining hardware, software, and firmware with diverse technologies including the Machine Learning and Artificial Intelligence, Internet of Things, creates an intelligent machine. People value and need it because it produces positive outcomes and makes efficient usage of resources. Effective equipment must be used to improve water quality, monitor humidity and increase crop yields. This article describes the latest technologies in agriculture for smart water systems using Artificial Intelligence and IoT. This article presents different equipment, modern irrigation systems, various comparisons and needs. Finally, various issues, problems and future directions for smart water management research are presented.